Impermeability Characteristics of Treated Marine Soft Soil with Ferronickel Slag Powder - Feng Chen; Shenghao Tong (Geofluids)
In order to study the law of evolution of erosion time on the impermeability of soil-cement in the marine environment, permeability tests, X-ray diffraction (XRD) tests, and scanning electron microscopy (SEM) tests were conducted on ferronickel slag powder (FSP) soil-cement. The changes in the permeability properties of the soil-cement under different soaking age conditions were investigated. The results show that the marine environment has little influence on the impermeability of soil-cement at an early age, and that their permeability coefficient is essentially identical to that of clear water. The impermeability of soil-cement in the marine environment decreases significantly after 28 days, and it continues to decrease with age. However, the deterioration in impermeability of soil-cement caused by the marine environment can be alleviated after FSP is added to the soil-cement, and a better mixing value of 40% is obtained. At the same time, the regression curve equation of the permeability coefficient of soil-cement with the change of age is established. FSP exerts a microaggregate effect and chemical activity in the soil-cement. It not only improves the compactness of the soil-cement matrix but also prevents the penetration of corrosive ions into the soil-cement, thereby improving the impermeability of the soil-cement.